Observational Effects on Preference Selection for Four Children on the Autism Spectrum: A Replication. (8th May 2015) - Leaf, Justin B.; Kassardjian, Alyne; Oppenheim‐Leaf, Misty L.; Tsuji, Kathleen H.; Dale, Stephanie; Alcalay, Aditt; Leaf, Jeremy A.; Ravid, Daniel; Miline, Christine; Leaf, Ronald; Taubman, Mitchell; McEachin, John
<x xml:space="preserve">Abstract</x> Individuals with autism have been noted to have restricted interests and repetitive behavior such as nonfunctional manipulation of objects. In this study, we used an observational conditioning procedure to switch the preference of items for four individuals diagnosed with autism who are considered lower functioning. The procedure consisted of the participant observing an adult playing with toys that were initially non‐preferred by the participant in a functional and engaging manner. For two participants, results were similar to the findings by Leaf; one participant required additional conditioning procedures, and we were unable to switch the preference for the other participant. Copyright © 2015 John Wiley & Sons, Ltd.